2011
DOI: 10.1182/blood-2011-06-363911
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib-induced “BRCAness” sensitizes multiple myeloma cells to PARP inhibitors

Abstract: Chromosomal instability is a defining feature of clonal myeloma plasma cells that results in the perpetual accumulation of genomic aberrations. In addition to its role in protein homeostasis, the ubiquitinproteasome system is also involved in the regulation of DNA damage-repair proteins. In the present study, we show that proteasome inhibition induces a "BRCAness" state in myeloma cells (MM), with depletion of their nuclear pool of ubiquitin and abrogation of H2AX polyubiquitylation, an essential step for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
143
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(153 citation statements)
references
References 47 publications
10
143
0
Order By: Relevance
“…130,131 The decrease in FANCD2 and H2Ax ubiquination by PI is explained by the accumulation of poly-ubiquitinated proteins and, consequently, the decrease of the pool of available nuclear ubiquitin. 132 Bortezomib treatment may prevent DNA resection through inhibiting proteasomal degradation of proteins involved in chromatin relaxation, thus preventing recruitment of RPA onto ssDNA. 130,131 This effect of Bortezomib on blocking DNA repair could explain why a phase II study has shown that the combination of Bortezomib together with highdose melphalan before autologous stem cell transplantation could increase by 3-fold the complete remission rate (35% vs. 11%).…”
Section: Dna Repair Pathways: Targets For Drugs Used To Treat MM Andmentioning
confidence: 99%
“…130,131 The decrease in FANCD2 and H2Ax ubiquination by PI is explained by the accumulation of poly-ubiquitinated proteins and, consequently, the decrease of the pool of available nuclear ubiquitin. 132 Bortezomib treatment may prevent DNA resection through inhibiting proteasomal degradation of proteins involved in chromatin relaxation, thus preventing recruitment of RPA onto ssDNA. 130,131 This effect of Bortezomib on blocking DNA repair could explain why a phase II study has shown that the combination of Bortezomib together with highdose melphalan before autologous stem cell transplantation could increase by 3-fold the complete remission rate (35% vs. 11%).…”
Section: Dna Repair Pathways: Targets For Drugs Used To Treat MM Andmentioning
confidence: 99%
“…13, 46,47 Targeted therapy has already demonstrated some efficacy, but may merely select for resistant subclones, unless a given mutation drives the disease as recently has been described for KRAS/NRAS activating mutations. 48 High-risk myeloma even with modern genetic analysis will likely remain a formidable opponent in years to come.…”
Section: Org Frommentioning
confidence: 99%
“…9,10 In MM cells, direct evidence of homozygous loss or mutations in BRCA1/2 or other DDR genes is lacking, but increased DNA repair activity has been reported. 11,12 Thus, identification of adaptive pathways for coping with genomic instability in MM may similarly provide the framework for new therapeutic strategies. …”
mentioning
confidence: 99%